Compression and relaxation properties of timothy hay - Talebi, S.; Tabil, L.; Opoku, A.; Shaw, M. (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: The compression and relaxation characteristics of timothy hay were investigated with respect to hay moisture content, applied load, and hay quality. Experimental trials were performed by using a Baldwin hydraulic universal testing machine model 60 HVL-1254. The applied loads ranged from 90 kN to 240 kN, in 30 kN increments. Two qualities of timothy hay were used, high quality with moisture contents of 7.44%, 10.17%, 12.97%, and 16.42% wet basis (w.b.), and low quality with moisture contents of 6.38%, 8.67%, 16.24%, and 18.94% w.b. The results indicated that the compact density of hay samples increased with increasing moisture content and applied pressure. Less maximum applied pressure was required to achieve the same compact density with increasing moisture content. Models were fitted to the applied pressure-compact density data. ?Relationships were developed between the model constants and the experimental variables. The use of Faborode-O